2013
DOI: 10.18553/jmcp.2013.19.7.534
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students Teaching Prescribers Strategies to Lower Prescription Drug Costs for Underserved Patients

Abstract: BACKGROUND: The rising costs of health care and, in particular, prescription drugs remains a challenge. Health professionals' ability to promote cost-effective prescription drug use is critical, yet this subject is not included consistently in the curriculum of most health professional schools. As experts in prescription drug selection, use, and cost, pharmacists are in a unique position to help manage prescription drug regimens for the best therapeutic outcome, while also helping to keep patients' out-of-pock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…6,11,17, A total of 15 articles originated from the USA, indicating a high interest in IPE programmes in this country. 11,[20][21][22][24][25][26]28,32,35,36,[38][39][40]42 For the rest, three studies each were conducted in the UK and Canada, two in Australia and one each in Sweden, Malaysia, the Philippines, China and Switzerland. 6,17,19,23,27,[29][30][31]33,34,37,41,43 Nine main strategies were identified for executing IPE activities: simulation-based education programmes; rotations in rural and community settings; interprofessional training wards; patient-centred case studies; theme-centred workshops; student seminars; student-delivered lectures; health promotion activities; and interactive lectures in a common setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,11,17, A total of 15 articles originated from the USA, indicating a high interest in IPE programmes in this country. 11,[20][21][22][24][25][26]28,32,35,36,[38][39][40]42 For the rest, three studies each were conducted in the UK and Canada, two in Australia and one each in Sweden, Malaysia, the Philippines, China and Switzerland. 6,17,19,23,27,[29][30][31]33,34,37,41,43 Nine main strategies were identified for executing IPE activities: simulation-based education programmes; rotations in rural and community settings; interprofessional training wards; patient-centred case studies; theme-centred workshops; student seminars; student-delivered lectures; health promotion activities; and interactive lectures in a common setting.…”
Section: Resultsmentioning
confidence: 99%
“…31,41,43 Lectures delivered by healthcare students to audiences composed of trainees from different disciplines were also utilised for IPE; these were reported to increase their confidence and awareness of future collaborative opportunities. 21,35,43 Students also formed interprofessional and collaborative teams in order to take part in community health promotion activities. 22,[36][37][38] Combined interactive lectures for students from various health professions also provided opportunities for student interaction and reflection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because pharmacists frequently encounter patients who need financial support for their medications, 48,49 they are in a unique position to help patients recognize the need to switch plans in a timely fashion, navigate plan alternatives, and provide medication cost-saving strategies. 50 Finally, addressing accuracy of information provided by people who assist Medicare beneficiaries in plan selection is critical. Several participants of our study reported they had been contacted by "Medicare people," who introduced available plans and led the beneficiaries in deciding between limited options offered by 1 commercial company.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is moderate evidence suggesting that pharmacists and student pharmacists may be appropriate and effective resources for Part D plan information. 4,5,8-10 Pharmacists have been shown to help beneficiaries identify more appropriate plan alternatives based on patient-specific characteristics; however, evidence of service use resulting in actual plan-switching decisions is lacking. This is the first study to evaluate a pharmacy-led Medicare Part D consultation effect on actual plan-switching decisions over the course of multiple open-enrollment periods for the Medicare Part D program.…”
Section: Introductionmentioning
confidence: 99%